PEMBUATAN GAME ADVENTURE PUZZLE “DARK SPIRIT ADVENTURE” BERBASIS WINDOWS PC - Sena, Arya; Pragantha, Jeanny; Haris, Darius Andana (Jurnal Ilmu Komputer dan Sistem Informasi, 2021)
Dark Spirit Adventure is a 2D puzzle platform game developed for Windows PC. This game was created using Unity game engine with C# as a programming language. The goal of this game is to complete all the stages and collect all the collectibles. At each stage, players will face various obstacles such as enemies, puzzles, and lights. Testing is done by blackbox testing, alpha testing by the supervisors, and beta testing by 31 respondents through an online questionnaire. The test results show that the game Dark Spirit Adventure entertains players, challenging players and has high replay value.